Contribution to the taxonomy and ecology of the Azorean benthic marine algae - Neto, Ana I. (1992)
Algal zonation patterns were studied in two sites (Caloura, south coast and Ribeirinha, north coast) of the island of São Miguel, Azores. At each site two stations were studied and the transects revealed the occurrence of two distinct and well established algal zones. In the first zone, daily immersed and emersed by the tide, the algae were growing in a dense and, short tangle forming a mat, referred to as algal turf. In the second zone, which was wet most of the time, the algae were larger and frondose. A list of the species of benthic marine algae occurring on the algal turf of each station is given. Of the total of 47 species found, eight are new for the Azores and another 13 species recorded for the first time for São Miguel. Gigartina acicularis (Roth) Lamouroux and articulate coralline algae (Corallina oficinalis Linnaeus and Jania spp.) were the more common species. Seasonal variation of the algal turf was studied and related to mean monthly values of air and sea water temperatures, insolation and hours of light. The zonation patterns and composition of algal species were compared with those from other open rocky shores.